Análisis jurídico y doctrinario de la consulta y el consentimiento previo como modelo generador de conflictos sociales: caso Gualel - Angamarca Bautista, Lady Estefanía (2023)
This thesis work is entitled "LEGAL AND DOCTRINARY ANALYSIS OF THE CONSULTATION AND PRIOR CONSENT AS A MODEL GENERATOR OF SOCIAL CONFLICTS: CASE GUALEL", understanding that the communities, peoples and nationalities that are in Ecuador have suffered various violations to their collective rights recognized in the Constitution of the Republic, we have focused on their right to be consulted on plans and programs for prospecting, exploitation and commercialization of non-renewable resources found on their lands and that may affect them environmentally or culturally, called prior, free and informed consultation, stipulated in article 57 numeral 7 of the supreme norm; as well as their right to be consulted before the adoption of a legislative measure that may affect any of their collective rights, under the figure of the Pre-Legislative Consultation, regulated in article 57 numeral 17 of the ibidem norm. Regarding article 398 of the Constitution of the Republic, which talks about the Environmental Consultation, it became necessary to investigate if the State is complying with the provisions of said article and is respecting this process of democratic participation in the rural town of Gualel Parish, Loja Canton, Loja Province, which is currently in the area of influence of mining projects. The research carried out aims to provide doctrinally relevant issues for these three types of consultation that have been proposed, so that it is understood what each of them refers to, as well as legally contribute to the analysis of laws and regulations, so that, hermeneutically an understanding of the issues raised is reached. Finally, guidelines have been proposed to reflect what is said by the International Instruments, and even the sentences issued by the Constitutional Court of Ecuador, due to the lack of appropriate guidelines to carry out the consultation, translated into citizen participation processes, considering so ignorance and misinformation can be a generator of social conflicts.